Generating employment, raising incomes and addressing poverty in Greece - Bulman, Tim (OECD Economics Department Working Papers, 2018)
Employment is pivotal to strengthening Greece's economic recovery, increasing social welfare and redressing poverty. Jobs are returning, making inroads into high unemployment, but their wages and skill levels are lower than many that were lost during the crisis. Greece's hiring is benefiting from more flexible arrangements. Legislative amendments can maintain this flexibility, ensure wages align with productivity and better protect individuals from labour market risks. Ensuring that workers possess skills that match employers' needs will sustain employment and productivity growth. Improving the education system is a long-term mission and involves raising its pedagogical strength and orientation towards professional needs. A social welfare system dominated by pensions has not been able to prevent a steep hike in poverty among children and the young, risking long-term harm to well-being. Pursuing recent steps towards a better targeted social protection, accompanied by support programmes for jobseekers, will provide a reliable safety net and reduce poverty. This Working Paper relates to the 2018 OECD Economic Survey of Greece. (http://www.oecd.org/eco/surveys/economic-survey-greece.htm)